Genetic diversity, correlation and path coefficient analysis of rajma bean (Phaseolus vulgaris) landraces in low altitude of Nagaland - THIRUGNANAVEL, A; DEKA, BIDYUT C; KUMAR, RAKESH; RANGNAMEI, LILY; MEYASE, MEGHOKHONO (The Indian Journal of Agricultural Sciences, 2019)
Thirty two rajma beans (Phaseolus vulgaris L.) landraces have been evaluated for 17 traits to study the genetic variability, correlations and direct and indirect effect of characters on yield. Results showed that wide range of variations were observed for all 17 traits among the landraces. Moderate to high level of GCV and PCV and high level of heritability were observed for all the traits. PCV was slightly higher than GCV, but the difference was insignificant. The traits such as plant height, number of seeds/plant, number of pods/plant, test weight and seed yield recorded high level of GCV, PCV and heritability. Correlation results showed that seed yield had positive and high correlation (p <0.01) with umber of seeds per plant, number of pods per plant, test weight and seed weight. It was observed that number of seeds per plant had high positive correlation with number of pods per plant and number of seeds per pod had high positive correlation with locules per pod. The results of path coefficient analysis showed that no. of seeds per plant and seed weight had very high level to high level of positive direct effect on seed yield. Based on findings, no. of seeds per plant, no. of pods per plant, test weight, no. of flowers per inflorescence and plant height are identified as very important traits in selection for improving the rajma bean yield.